Penerapan Pendekatan Science Environment Technology and Society (Sets) untuk Meningkatkan Literasi Sains Siswa di Sekolah Dasar - Enggi Julianto (Publikasi Indonesia, 2022)
This study was motivated by the low science literacy skills of Class VI students in science learning. The purpose of this study was to describe the implementation of learning using the SETS approach in science learning and the results of improving students' science literacy. The research method to be used is classroom action research by adapting the model of Kemmis and Taggart which is carried out with 2 cycles. The research subjects were 6th grade students at SDS 023 Astra Agro Lestari with a research focus of 15 students. The results of this study indicate that: (1) The implementation of science learning in environmental pollution material was carried out well by teachers and students. (2) The increase in students' science literacy in each cycle is very high with an average of 48.42 (pretest), 75.78 (cycle 1), and 87.89 (cycle 2).